Conceptualisation of mental illness by vhaVenda indigenous healers - Sigida, Salome Thilivhali (University of Limpopo, 2016)
Several studies have shown that alternative health care practitioners play an important role in addressing the mental health care needs of individuals by offering culturally appropriate treatment. In South Africa, it has been suggested that indigenous healers are frequently consulted for mental illness when compared to their Western trained counterparts. The aim of the present study was to explore the conceptualization of mental illness by VhaVenda indigenous healers. Specifically, the study sought to achieve the following objectives: a). Establish what VhaVenda indigenous healers understand about mental illness; b). Determine the types of mental illness identified by VhaVenda indigenous healers; and, c). To determine what indigenous healers in this community perceive as the signs and symptoms of mental illness. A qualitative approach, and in particular, the case study method was used in the present study. Ten indigenous healers (male = 8: female = 2), aged between 35 and 60 were selected through snowball sampling and requested to participate in the study. Data were collected using semi-structured interviews and analysed using the content analysis method. The following psychological themes emerged from the study: a). participants understanding of mental illness; b). causes of mental illness; c). types of mental illness; d). signs and symptoms of mental illness; e). diagnoses of mental illness and f). Treatment of mental illness. The findings revealed that there are multiple causalities of mental illness and were accounted for by African indigenous beliefs. The findings of the present study further suggested that the participants do not have an elaborate nosological system that distinguishes between the different types of mental illness. Instead of giving names to the illnesses, the participants tended to describe the illness based on what is perceived as the cause which emanate from cultural ideologies. Furthermore, the results revealed that indigenous healers use the following treatment modalities to treat mental illness: namely, the use of herbs and indigenous practices. The study is concluded by making a few recommendations, that among others include consideration been given to some form of collaboration between indigenous healers and western trained health care practitioners.
Thesis (M. A. (Psychology)) -- University of Limpopo, 2016
Keywords: Mental illness; Indigenous healers; Venda (African people).; Mental illness -- South Africa; Herbalists -- South Africa -- Limpopo.